Unterstützung des Variantenmanagements von Elektromotoren durch wissensbasierte Systeme - Tüchsen, Johann; Dorsch, Julian; Obendorfer, Moritz; Schleich, Benjamin; Wartzack, Sandro (Design for X. Beiträge zum 30. DfX-Symposium 2019, 2019)
The automotive industry electrifies a huge variety of previously mechanically-actuated car functions. While sharing the same function. the used electric motors often differ in customer related geometries and interfaces. The suppliers have to cope with this huge external variance using an appropriate variant management. With this paper. the support of the variant management of electric drives by knowledge-based systems is proposed. Therefore. a combination of two systems containing the knowledge of the configuration and design of motors are used. The concept is applied and evaluated on the example of the shaft rotor lamination connection. As a result. the amount of internal variants can be reduced and controlled as well as the designer can be supported during the development process.<br
Keywords: Variant Management; Knowledge-based Systems; KBS; Electric Drives